Hubungan Dukungan Keluarga dengan Tingkat Kekambuhan Pasien Skizofrenia di Wilayah Kerja Puskesmas Katumbangan - Nurlina Nurlina; Fredy Akbar; Hermin Manganan (Yayasan Mandar Indonesia, 2026)
Schizophrenia is a chronic mental disorder characterized by disturbances in thought processes, emotions, and behavior, with a high risk of relapse when patients do not receive adequate family support. Family support plays an important role in treatment adherence and relapse prevention among individuals with schizophrenia. This study aimed to determine the relationship between family support and relapse levels among patients with schizophrenia in the working area of Katumbangan Primary Health Center. This study employed a quantitative approach with a cross-sectional design. The study population consisted of 61 schizophrenia patients, all of whom were included as respondents using a total sampling technique. Data were collected using a family support questionnaire and a schizophrenia relapse questionnaire. Data were analyzed using Fisher’s Exact Test with a significance level of p < 0.05. The results showed that most respondents had inadequate family support (86.9%) and a high level of relapse (62.3%). Analysis using Fisher’s Exact Test revealed a significant relationship between family support and relapse levels among patients with schizophrenia (p < 0.001). The study concluded that family support is significantly associated with relapse levels in patients with schizophrenia. Adequate family support may help reduce the risk of relapse. Therefore, families are encouraged to provide emotional, informational, and instrumental support, while primary health centers should enhance educational programs related to schizophrenia patient care.